Divine Scripture and Human Emotion in Maximus the Confessor : Exegesis of the Human Heart - Summerson, Andrew J., (The Bible in Ancient Christianity ;, 2021)
"In Exegesis of the Human Heart Andrew J. Summerson explores how Maximus the Confessor uses biblical interpretation to develop an account of human passibility, from fallen human passions to perfected human emotions among the divinized. This book features Maximus's role as a creative interpreter of tradition. Maximus inherits Christian thinking on emotion, which revises Stoic and Platonic thought according to biblical categories. Through a close reading of Quaestiones ad Thalassium and a wide selection of Maximus's works, Andrew J. Summerson shows that Maximus understands human emotion in an exegetical milieu and that Maximus places human emotion at the heart of his soteriology. Christ redeems passibility so the divinized can enjoy perfected emotional activity in the ever-moving repose of eternal life"--